The evaluation of the global energy and fuels research: A scientometric approach - Konur, Özcan (SILA SCIENCE, 2012)
The present study explores the characteristics of the global energy and fuels literature published between 1945 and 2011 based on the Arts & Humanities Citation Index (A&HCI), Science Citation Index Expanded (SCIE), and Social Sciences Citation Index (SSCI) and its implications using the scientometric techniques. The results of this study reveal that the energy and fuels research output have grown spectacularly starting with 86 papers in 1972 and ending with 16,333 papers in 2011, showing superb performance in the 2000s triggered by the 2001 Twin-Tower terrorist attacks renewing the global anxiety on the energy supplies, with paralleling enormous changes in the research landscape. There were 150,253 papers published between 1972 and 2011 comprising 0.5% of the global literature indexed by the A&HCI, SSCI, and SCIE between 1945 and 2011. The US, China, and Japan have been the three most prolific countries. The "Indian Inst Technol" of India has been the most prolific institution and "Probert SD" of the Cranfield University has been the most prolific author. "Journal of Power Sources" has been the most prolific journal whilst "Energy Fuels" has been the most prolific subject area. A review paper on the nitrogen chemistry in combustion has had the highest impact on the literature with 1,565 citations. The scientometric analysis has a great potential to gain valuable insights into the evolution of the global research on the energy and fuels, complementing the scientometric studies in the fields of the renewable energies as well as other dynamic research fields providing a unique insight on the incentive structures for all the key stakeholders in the field.
Keywords: Energy; Fuels; Research evaluation; Research productivity; Scientometrics; Web of Knowledge